PENERAPAN METODE HAAR CASCADE PADA APLIKASI DETEKSI MASKER - Aprilian Anarki, Galang; Auliasari, Karina; Orisa, Mira (Institut Teknologi Nasional Malang, 2021)
This research aims to create an application that can detect the use of masks to minimize the transmission of the Covid-19 virus, which is currently an epidemic in Indonesia, by issuing an audio warning feature and taking pictures if a mask is not detected.This study using the Haar Cascade method. Haar Cascade is an object detection method created by Paul Viola and Michael Jones. In 2001, they presented a paper called